Characteristics and clinical course of myoclonus in Cavalier King Charles Spaniels - Matthew James; Mark Lowrie; Clare Rusbridge (Journal of Veterinary Internal Medicine)
Abstract Background Myoclonus has been described in aging Cavalier King Charles Spaniels (CKCS), but the natural course of the disease and response to treatment have not been described. Objectives Report the clinical features and course of myoclonus in CKCS. Animals Twenty‐seven caregivers provided questionnaire responses at a median of 24 months after the onset of myoclonus in their CKCS. Fifteen caregivers completed a second follow‐up questionnaire at a median of 17 months after submission of the first questionnaire. Methods The caregivers of affected CKCS were invited to provide video footage for review. Owners of CKCS with videos demonstrating myoclonus then completed the online questionnaire for further evaluation. A second shortened questionnaire was sent to participants at least 6 months after completion of the first. Results Most CKCS displayed spontaneous myoclonus affecting predominantly the head (25/27). Overall, the majority had episodes that increased in frequency (20/27) and severity (17/27). Eighteen dogs had developed changes in behavior since the onset of myoclonus. These dogs were typically older and had experienced myoclonic episodes for longer than dogs without behavioral changes. Generalized epileptic seizures were reported in 4/27 dogs. Ten dogs received medical treatment. Eight were prescribed levetiracetam; all had an initial decrease in episode frequency, but a subsequent increase in both frequency and severity of episodes was common. Conclusions and Clinical Importance Myoclonus in CKCS tends to progress in frequency and severity regardless of treatment. Progressive behavioral changes suggestive of cognitive decline are common. These findings support the possibility of an underlying neurodegenerative process.